IMPROVING STUDENTS’ READING COMPREHENSION BY USING THINK PAIR SHARE TECHNIQUE IN ONE OF JUNIOR HIGH SCHOOL IN KARAWANG. - YOGI SETIA SAMSI; ANNA APRIYANA RAHAYU (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2016)
The objective of this research is to find out that think pair share technique in improving students’ reading comprehension. The research method used in this research was quasy experimental method. This research conducted at eighth grade students of SMPN in Karawang. The procedures of research in experiment are giving pre-test, treatment, and giving posttest. The data gathered in this research was through pre-test and post-test. The result of this research showed that there was differences between teaching using think pair share technique and conventional method. In analyzing data, the researcher used independent T-test in SPSS version 22 at the level of significance 95% (α 0,05), and compared with T-table. The researcher got7.641. This obtained T-value exceed the critical values for two tiled test under p= 0,05 (1, 668).The conclusion in this research, there is improving of think pair share technique for readingcomprehension